Impact of milk production and important management factors on the process of dry-off in lactating dairy cows - Dingwell, R.T.; Leslie, K.E.; Sargeant, J.M.; Schukken, Y.H.; Timms, L.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study of 250 cows located in Canada and the United States revealed the rate of new mammary infections was 9.9% during the dry period. Average milk production on the day prior to dry-off was 13.2 ± 7.2 kg. The odds of a cow developing a new infection was three times greater if the cow was producing more than 5 kg of milk. After 6 weeks of the dry period, 25% of the teats still remained open. This research will serve as the foundation to investigate and implement management strategies prior to dry-off that might improve the overall udder health of dairy cows.
Keywords: Dairy; Dry-off; Mastitis; Milk production